In Situ Analytical Techniques for the Investigation of Material Stability and Interface Dynamics in Electrocatalytic and Photoelectrochemical Applications. Issue 7 (16th June 2021) - Pishgar, Sahar; Gulati, Saumya; Strain, Jacob M.; Liang, Ying; Mulvehill, Matthew C.; Spurgeon, Joshua M.
Abstract: Electrocatalysis and photoelectrochemistry are critical to technologies like fuel cells, electrolysis, and solar fuels. Material stability and interfacial phenomena are central to the performance and long‐term viability of these technologies. Researchers need tools to uncover the fundamental processes occurring at the electrode/electrolyte interface. Numerous analytical instruments are well‐developed for material characterization, but many are ex situ techniques often performed under vacuum and without applied bias. Such measurements miss dynamic phenomena in the electrolyte under operational conditions. However, innovative advancements have allowed modification of these techniques for in situ characterization in liquid environments at electrochemically relevant conditions. This review explains some of the main in situ electrochemical characterization techniques, briefly explaining the principle of operation and highlighting key work in applying the method to investigate material stability and interfacial properties for electrocatalysts and photoelectrodes. Covered methods include spectroscopy (in situ UV–vis, ambient pressure X‐ray photoelectron spectroscopy (APXPS), and in situ Raman), mass spectrometry (on‐line inductively coupled plasma mass spectrometry (ICP‐MS) and differential electrochemical mass spectrometry (DEMS)), and microscopy (in situ transmission electron microscopy (TEM), electrochemical atomic force microscopy (EC‐AFM), electrochemical scanning tunneling microscopy (EC‐STM), and scanning electrochemical microscopy (SECM)). Each technique's capabilities and advantages/disadvantages are discussed and summarized for comparison. Abstract : In situ analytical techniques for electrochemical applications, including spectroscopy, mass spectrometry, and microscopy methods, are reviewed in the context of electrocatalysis and photoelectrochemistry. Each technique's working principle, the necessary modifications for in situ electrochemical operation, and the relative advantages and disadvantages for researchers are discussed, and state‐of‐the‐art applications in catalysis and solar energy are reviewed.